Comparative Essential Oil Analysis of Calendula arvensis L. Extracted by Hydrodistillation and Microwave Distillation and Antimicrobial Activities - Tosun, Gonca; Yayli, Busra; Arslan, Tayfun; Yasar, Ahmet; Alpay Karaoglu, Sengul; Yayli, Nurettin (Asian Journal of Chemistry, 2011)
The present study was to investigate the influence of the extraction methods on yield and chemical composition of the essential oil of Calendula arvensis L. The volatiles of C. arvensis have been isolated by hydrodistillation (HD) and microwave distillation (MD). The compositions of the essential oils were characterized by GC-FID and GC-MS. A total of 45 and 44 compounds were identified, constituting over 88.3 % and 84.8 % of oil composition of C. arvensis, respectively. Sesquiterpenes (HD: 30.5 % and MD: 23.4 %) and monoterpene compounds (HD: 26.3 % and MD: 24.3 %) were shown to be the main group of volatiles. The major terpene constituent of the essential oils of C. arvensis was a-selinene (HD, 16.0 % and MD, 0.0 %), a-pinene (HD, 11.9 % and MD, 12.3 %), (Z)-a-santalol (HD, 8.2 % and MD, 7.4 %), d-amorphene (HD, 0.0 % and MD, 8.0 %), (Z)-sesquilavandulol (HD, 4.8 % and MD, 0.0 %), 7-epi-silphiperfol-5-ene (HD, 2.6 % and MD, 3.7 %), viridiflorene (HD, 2.5 % and MD, 1.7 %) and b-pinene (HD, 1.8 % and MD, 2.4 %). Comparative study showed that the amount of total volatiles (88.3 % and 84.8 %) and the identified constituent (45 and 44) were found to be similar in both HD and MD of C. arvensis. The terpenoid contents (HD: 73.5 % and MD: 65.3 %) were greater in HD of C. arvensis. The antimicrobial activities of the isolated essential oils, hexane, ether and methanolic extracts of the plant were also investigated and only the essential oil (HD) and methanolic extract showed moderate antibacterial activities against Staphylococcus aureus and Bacillus cereus with in the range of 105-210 μg, respectively. But all the extract showed good antituberculose activity against Mycobacterium smegmatis (13.2-62.5 μg).